The main psychological determinants of the participants’ readiness of professional skill competitions to perform successfully - E. V. Pugacheva; A. Yu. Tymchikov (Вестник университета)
The article presents the results of psychological research and the primary analysis of the results obtained, which allow us to formulate the main psychological determinants of the readiness of the contestants for competitions in professional skills and possible success. The study was conducted by means of questionnaire methods, primary statistical processing (percentage ratio), comparative analysis of the data obtained. The object of the study was the participants of professional skill competitions: winners, prize-winners and contestants who performed unsuccessfully. It was revealed that the winners and prize-winners of professional skill competitions, as well as participants who performed unsuccessfully, actively use psychological and professional techniques, techniques, creativity, and so on in preparation for competitions. The personal and professional qualities of the contestants contributing to their success and possible reasons for unsuccessful performances are noted. The main psychological determinants of the contestants’ readiness for competitions in professional skills and possible success are identified and formulated – personality strength; confidence; a high level of need for achievements and victories; an adequate level of self-esteem; a high level of reflection; competent knowledge of psychological technologies of self-action; a high level of personal and professional qualities development; rational independence in preparation.